2016
DOI: 10.4103/1463-1741.195796
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette- and snus-modified association between unprotected exposure to noise from hunting rifle caliber weapons and high frequency hearing loss. A cross-sectional study among swedish hunters

Abstract: Aim:To investigate in this cross-sectional study among Swedish hunters if tobacco use modifies the previously observed association, expressed as prevalence ratio (PR), between unprotected exposure to impulse noise from hunting rifle caliber (HRC) weapons and high-frequency hearing impairment (HFHI).Settings and Design:A nationwide cross-sectional epidemiologic study was conducted among Swedish sport hunters in 2012.Materials and Methods:The study was Internet-based and consisted of a questionnaire and an Inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…If a similar mechanism exists in the cochlea, we speculate that some SGNs in chronically CS-exposed mice could have a lower threshold for activation, driving oxidative stress. Notably, a study that compared hearing loss in hunters who either smoked or chewed tobacco found that both groups had greater hearing loss than hunters who did not do either, suggesting a specific role for nicotine 48 . Upregulation of Chrna9 and Chrn10 in OHCs might also explain the associated enlarged MOC terminals.…”
Section: Discussionmentioning
confidence: 99%
“…If a similar mechanism exists in the cochlea, we speculate that some SGNs in chronically CS-exposed mice could have a lower threshold for activation, driving oxidative stress. Notably, a study that compared hearing loss in hunters who either smoked or chewed tobacco found that both groups had greater hearing loss than hunters who did not do either, suggesting a specific role for nicotine 48 . Upregulation of Chrna9 and Chrn10 in OHCs might also explain the associated enlarged MOC terminals.…”
Section: Discussionmentioning
confidence: 99%